The Role of Teamwork in Building Patient Safety Culture at Hospital “X” in South Jakarta, Indonesia - Shameela, Alika; Sulistiadi, Wahyu (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: Patient safety is an important discipline for improving the quality of hospital health services.  By establishing a positive patient safety culture in a hospital, the commitment to create a safer patient safety culture as an act to reduce incidents is also higher.  One of the supporting factors of patient safety culture is teamwork. Teamwork is an effort to work with other people cooperatively as a part of the group. Hospital "X" is a hospital located in  South  Jakarta that in carrying out their mission to improve the quality of their health services, requires a positive patient safety culture. Objective: This research aims to analyze the role of teamwork in building a safer patient safety culture at Hospital “X". Method: This research is qualitative research with a case study approach using in-depth interviews with    4 informants.   The research was conducted in   August- September 2023. Result: The results of the research show the patient safety culture in Hospital "X". Hospital Hospital  "X"  already has a fairly positive patient safety culture by having a patient safety program and good teamwork,  but still needs more evaluation on its implementation. In addition, teamwork has an important role in building a patient safety culture in terms of team effectiveness, support for staff, as well as regular reviews and evaluations of the team.  Conclusion:  The patient safety program at Hospital “X” already exists and has been running quite well.    The factors contributing are teamwork and collaboration, but the effectiveness of teamwork is still not quite effective. Recommendation: Therefore, a tiered guidance supervision system is recommended along with a regular seminar or training and support management